Acute Effects of a Simulated Karate Bout on Muscular Strength Asymmetries of the Lower Limbs in Elite Athletes of Different Age Categories - Eliza Gaweł; Miłosz Drozd; Adam Maszczyk; Adam Zając (Applied Sciences)
This study aimed to assess the acute impact of a simulated kumite bout (WKF formula) on peak isometric strength performance of the dominant and non-dominant lower limbs in elite karate athletes of different age categories (U16, U18, Senior), in the context of inter-limb asymmetry. Sixty-one elite male and female athletes (age = 17.48 ± 3.26 [years], body height = 1.72 ± 0.08 [m], body mass = 63.79 ± 10.00 [kg]) participated in this study, which included a randomized crossover design (two experimental sessions under two different conditions). Inter-limb asymmetry was assessed based on the isometric mid-thigh pull test. Friedman’s test indicated significant differences in the mean values of the peak vertical force (PVF) between the assessed limbs (test = 10.8; p = 0.013; Kendall’s W = 0.059). Elite karate athletes, regardless of the age category, tend to have inter-limb strength asymmetries in the lower extremities; however, the impact of a simulated kumite bout was not fully confirmed. A kumite bout seems to have a favorable impact on bilateral asymmetries in U16 and U18 athletes, but not in Seniors, who seem to be at increased risk of injury after completing the bout (asymmetry > 15%). Limb dominance is not necessarily related to greater values of PVF.